Mercados alimentares digitais da agricultura familiar no Brasil : dinâmicas durante e pós pandemia da COVID-19 - Gazolla, Marcio (Mundo Agrario.)
This article aims to analyze the dynamics of digital food markets of Brazilian family farming during and after the Covid-19 pandemic. To this end, methodologically, the netnography technique was used to identify and evaluate digital marketing experiences by websites and platforms distributed throughout the national territory, in 2020 and 2022. In general terms, the study shows that digital marketing channels of food have been strengthened in Brazil, observing the maintenance and increase in the number of family farmers and participating enterprises, as well as the types of products offered. The largest contingent of family farmers involved in the experiences studied is located in the South and Northeast regions, stimulated by cooperation. The main foods offered are in natura, agro-industrialized and ecological, showing that digital markets have directly contributed to a part of the country's consumers that seek healthy and sustainable diets. Despite these virtues, these new commercialization channels need support from the State to guarantee their improvement and include larger portions of national family farming.